Alterations in interpersonal relations in borderline personality disorder: loneliness, rejection, and belonging - Liebke, Lisa (2019)
Borderline personality disorder is characterized by severe alterations in interpersonal relations that are described as a pattern of unstable and intense interpersonal relationships and frantic efforts to avoid real or imagined abandonment. According to important theoretical frameworks, problems in interpersonal relationships can be both cause and consequence of borderline personality disorder. The overall aim of the present thesis is to gain deeper insight into important aspects of interpersonal relations that might be especially altered in borderline personality disorder: Loneliness, rejection, and belonging. These three concepts are interrelated, since social rejection threatens the fundamental need to belong, and hence can contribute to opposite feelings, like loneliness. Loneliness, i.e., the subjective feeling of being socially isolated, has been shown to cause fundamental burden to social interaction, health, and well-being. Although generally it has been linked to aspects of social networks and social functioning that are known to be altered in patients suffering from borderline personality disorder, empirical data focusing specifically on the role that loneliness plays in these patients’ lives was lacking so far. Hence, in study I, we started to close this gap, confirming that borderline personality disorder patients report remarkably increased levels of loneliness. Moreover, they report smaller and less diverse social networks, as well as lower social functioning across all assessed domains of social skills and behaviors, when compared to healthy individuals. In addition to factors that are related to increased loneliness in general (i.e., small network size and low functioning in the domains of social engagement and prosocial behavior), we identified aspects with particular relevance for loneliness in borderline personality disorder (i.e., diversity of social networks and reduced interpersonal communication). Since after controlling for effects of social network features and social functioning, loneliness scores were still increased, further factors contributing to the painful experience of loneliness in borderline personality disorder need to be investigated in future research. Thus, study I is only a first step in understanding loneliness in borderline personality disorder, nonetheless providing important starting points to determine an approach that might improve these persistent negative social feelings in this clinical sample. After investigating loneliness as an affective subcomponent of social relatedness in study I, in study II and III we were interested in the effects of social rejection and acceptance on social cognition and interpersonal behavior. Since the paradigm used to induce social rejection and acceptance has been shown to be crucial, we developed a new paradigm specifically tailored to our research needs: The Mannheim Virtual Group Interaction Paradigm. Along with testing the ecological validity of the Mannheim Virtual Group Interaction Paradigm, in study II, we were particularly interested in whether the degree of affiliation with social partners would affect the degree and the adjustment of expectations of social acceptance and the adjustment of arousal over the course of repeated experiences of acceptance or rejection. Our findings revealed that expectations change very quickly after experiences of acceptance or rejection. Furthermore, expectations were influenced by affiliation particularly in case of positive social feedback of acceptance, whereas the adjustment of expectations after rejection was not affected by the degree of affiliation. Contrarily, subjects with higher affiliation responded to social rejection with a stronger increase in psychophysiological arousal, particularly during rejection feedback. This supports the idea that becoming part of a group and avoiding rejection constitute distinct domains of affiliation. Moreover, our findings emphasize the need to use social rejection paradigms that include a phase during which participants have the opportunity to create bonds with future executors of rejection or acceptance. Hence, the use of a virtual approach which allows people to become acquainted seems to be a promising approach, combining mundane realism with high experimental control. In study III, we extended our investigations of study II to a comparison between healthy indi-viduals and patients with borderline personality disorder. Our findings support the assumption that expectations of social acceptance are reduced in borderline personality disorder. Most importantly, they clearly reveal alterations particularly in case of positive social interaction: Patients failed to adjust their expectations to positive feedback, and instead responded with anger and behaved less cooperative towards cooperating interaction partners in a different social context after feedback of social acceptance. These findings suggest deficits in the appraisal and integration of signals of social acceptance in borderline personality disorder. Alterations during the processing of positive social cues disadvantageously affect social encounters in subsequent independent social situations, i.e., interpersonal problems may arise if an interaction partner behaves fair, and the patients were previously confronted with social acceptance of others that violated their expectations. Hence, study III exposes that patients with borderline personality disorder do not only fear and avoid rejection, but also exhibit non-negligible difficulties with becoming part of a dyad or group and developing a sense of belonging. Taken together, the present thesis emphasizes tremendous alterations in interpersonal rela-tions in borderline personality disorder throughout emotional experiencing (heightened loneliness), cognitive processing (reduced expectations of social acceptance and a failure to update these expectations according to positive social information), and social interaction (reduced cooperative behavior towards a cooperating interaction partner after an independent social encounter that provided feedback of social acceptance). Increased feelings of loneliness as well as the mismatch of expectations and experiences of social acceptance together with resulting consequences for interpersonal relations should be targeted in future research and hereafter in the development of psychotherapeutic interventions.